Relationship between the frequency of playing online games and the habit of consuming high-sugar drinks on adolescent - Suwarsi, Suwarsi; Mindarsih, Eko; Reboldera Adolfo, Melanie (JHeS (Journal of Health Studies), 2024)
Background: Online gaming has become increasingly popular in recent years, with millions of people worldwide spending hours every day playing games. While there are many benefits to playing online games, such as improved hand-eye coordination and problem-solving skills, there are also some potential risks, such as developing unhealthy habits. One of these habits is consuming drinks high in sugar. Objectives: This research contributed to nurses as preventive and promotive programs at school or in the community. Method: A cross-sectional study was conducted to identify the relationship between online gaming and the consumption of high-sugar drinks. Samples were taken from adolescents aged 15-23 years. The sample selection was carried out by chance in youth gathering areas such as cafes, The sample formula was taken using the Slovin formula, with the results being 60 samples. The research was conducted from July to August 2023 in Depok Sleman, Indonesia. Results: The study found a significant relationship between the frequency of playing online games and the habit of consuming drinks high in sugar. The more time people spend playing online games, the more likely they are to consume sugary drinks.